La narration dans la formation des professionnels de santé travaillant avec des personnes atteintes de démence : quel(s) usage(s) ? - Silvia Rossi
Narrative medicine helps doctors to understand what they and their patients experience in the presence of illness (Charon, 2006/2015). On the basis of the work of Rita Charon, I assume that narrative medicine tools - attention, representation and affiliation - can be effectively employed in the training of medical staff working with people with dementia. I tested my hypothesis in a training session for multi-professional healthcare providers' at the nursing home Casa Amica (Lamezia, Italy). In this paper, I present the design and the setting up of the phases of this training session: (1) create a framework to allow the expression of people with dementia (two individual interviews); (2) close reading of the collected material and recording of a video summary; (3) collective discussion of the project. My work demonstrates that narrative medicine tools, originally conceived for the doctor / patient relationship, can be effectively employed in a multi professional context; they allow healthcare providers to engage a collective thinking about their practice and improve the relationship between caregivers and people with dementia.